Measuring and Modeling Hydraulic Lift of Lolium multiflorum Using Stable Water Isotopes. Issue 1 (18th May 2017) - Meunier, Félicien; Rothfuss, Youri; Bariac, Thierry; Biron, Philippe; Richard, Patricia; Durand, Jean-Louis; Couvreur, Valentin; Vanderborght, Jan; Javaux, Mathieu
Abstract : Core Ideas: An experimental setup was designed to observe and accurately locate hydraulic lift. Water stable isotope enrichment was observed in topsoil layers. The results could be successfully reproduced using a 3D soil–root model. This study tested a method to quantify and locate hydraulic lift (HL, defined as the passive upward water flow from wetter to dryer soil zones through the plant root system) by combining an experiment using the stable water isotope 1 H2 18 O as a tracer with a soil–plant water flow model. Our methodology consisted in (i) establishing the initial conditions for HL in a large rhizobox planted with Italian ryegrass ( Lolium multiflorum Lam.), (ii) labeling water in the deepest soil layer with an 18 O‐enriched solution, (iii) monitoring the water O isotopic composition in soil layers to find out changes in the upper layers that would reflect redistribution of 18 O‐enriched water from the bottom layers by the roots, and (iv) comparing the observed soil water O isotopic composition to simulation results of a three‐dimensional model of water flow and isotope transport in the soil–root system. Our main findings were that (i) the depth and strength of the observed changes in soil water O isotopic composition could be well reproduced with a modeling approach (RMSE = 0.2‰, i.e., equivalent to the precision of the isotopic measurements), (ii) the corresponding water volume involved in HL was estimated to account for 19% of the plant transpiration of the following day, i.e., 0.45 mm of water, and was in agreement with the observed soil water content changes, and (iii) the magnitude of the simulated HL was sensitive to both plant and soil hydraulic properties.